Faces of the wolf : managing the human, non-human boundary in Mongolia - Charlier, Bernard (Inner Asia book series, 2015)
In his study of the human, non-human relationships in Mongolia, Bernard Charlier explores the role of the wolf in the ways nomadic herders relate to their natural environment and to themselves. The wolf, as the enemy of the herds and a prestigious prey, is at the core of two technical relationships, herding and hunting, endowed with particular cosmological ideas. The study of these relationships casts a new light on the ways herders perceive and relate to domestic and wild animals. It convincingly undermines any attempt to consider humans and non-humans as entities belonging a priori to autonomous spheres of existence, which would reify the nature-society boundary into a phenomenal order of things and so justify the identity of western epistemology.